MICROWAVE DIELECTRIC PROPERTIES OF Ba0.75Sr0.25 (NdxBi1-x)2Ti4O12 SOLID SOLUTION - Long Mingzhu; ZHuang WENDONG; Tang Bin; Yu Shengquan; Zhou Xiaohua; Zhang Shuren (Ceramics-Silikáty, 2011)
This work investigated the influences of Bi content on the phase structure, phase composition, microstructure and microwave properties of tungstenbronze-type like Ba0.75Sr0.25(NdxBi1-x)2Ti4O12 ceramics. XRD patterns showed that the main crystal phase of the ceramics with different Bi content (0.75 ≤ x ≤ 0.9) sintered at 1250°C to 1400°C for 3 h was BaNd2Ti4O12 with small amount of second phase Ba2Ti9O20. SEM photographs suggest that Bi could work as sintering aids promoting the densification and grain growth. In the case of the ratio of Nd and Bi (x : (1-x)) is 3:1 namely x is 0.75(B13), this ceramic shows optimum dielectric properties with a high dielectric constant (ε) of 118.5, a quality factor (Q × f) of 4907 (f = 2.8 GHz), and a temperature coefficient of resonant frequency tf = –1.3 ppm/°C. As the addition of Bi increased from 0.1 to 0.25, the value of ε markedly increased, the value of Q × f and tf decreased with a tf value finally approaching to zero.